Bone and Muscle Crosstalk in Aging - He, Chen; He, Wenzhen; Hou, Jing; Chen, Kaixuan; Huang, Mei; Yang, Mi; Luo, Xianghang; Li, Changjun (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis and sarcopenia are two age-related diseases that affect the quality of life in the elderly. Initially, they were thought to be two independent diseases; however, recently, increasing basic and clinical data suggest that skeletal muscle and bone are both spatially and metabolically connected. The term “osteosarcopenia” is used to define a condition of synergy of low bone mineral density with muscle atrophy and hypofunction. Bone and muscle cells secrete several factors, such as cytokines, myokines, and osteokines, into the circulation to influence the biological and pathological activities in local and distant organs and cells. Recent studies reveal that extracellular vesicles containing microRNAs derived from senescent skeletal muscle and bone cells can also be transported and aid in regulating bone-muscle crosstalk. In this review, we summarize the age-related changes in the secretome and extracellular vesicle-microRNAs secreted by the muscle and bone, and discuss their interactions between muscle and bone cells during aging.